Transformation of COVID-19 Related Terms in Jakarta Post, BBC, and CNN Portals: Analyzing Word Formation Processes - Rosyadah, Nabilah (Journal of Literature, Linguistics, & Cultural Studies, 2023)
The global pandemic known as Coronavirus Disease 2019 (COVID-19) has an impact on the use of language. The language used in COVID-19 news is frequently unfamiliar to the general public or even made up just for the pandemic. The goal of this study is to examine the word formation of COVID-19-related terms used in The Jakarta Post, BBC, and CNN portals. There are two research questions in this study, they are: (1) What are the types of word formation processes found in terms related to COVID-19? (2) How are the words related to COVID-19 formed? Moreover, this research uses Lieber’s theory (2016). This study uses a qualitative methodology. The findings of this study show that there are seven types of word formation: affixation, compounding, coinage, backformation, blending, clipping, and acronyms and initialisms. The conversion type is the process of word formation that has not been discovered. Words related to COVID-19 are formed by adding or removing an affix, combining or blending two words, expressing a specific object, and abbreviating a word. It can be concluded that many terms related to COVID-19 are the result of a word formation process that aims to form new words that will certainly give different meanings and different word classes from the original word. In the future, this research can be useful for readers who are looking for definitions of terms related to COVID-19, as well as for those who are interested in morphology or the field of word formation processes.